Does Parental Involvement Change After Schools Assign Students an IEP?. Issue 1 (1st January 2022) - Kirksey, J. Jacob; Gottfried, Michael A.; Freeman, Jennifer A.
ABSTRACT: Researchers suggest that parental involvement is important for parents of students with disabilities. While some research has examined parental involvement in the special education process, no research has investigated how general forms of parental involvement changes once a child begins to receive special education services. We consider various forms of parent involvement to exist within microsystems (e.g., home-based involvement) and mesosystems (e.g., school-based involvement) and how these actions are shaped by different factors of exosystems (e.g., neighborhoods) and the overarching macrosystems (e.g., poverty). With this framework, we consider the extent to which parental involvement changes for parents of students with disabilities following the assignment of the child's Individualized Education Program (IEP). Specifically using the ECLS-K: 2011, we exploit variation in home-based involvement, school-based involvement, and home-school communication based on children who have an IEP in one year but not the year before or after. Findings suggest that parents increased their home-based involvement actions following IEP assignment, though this was especially pronounced for parents from historically disenfranchised backgrounds. Findings also suggest that parents of English-language learners and second-generation students and parents in urban areas were more likely to increase their school-based involvement actions following IEP assignment.